(3GdaUjMs - (3CHh GdYHGS CMeO Hf jMji Hf RjO KYdH GdTjHGfj Gdchaj GdfMhj,J (B291 (3g` s ((3GHh GdaJhM YHjO Gddg Hf CHj GdeYeQ Hf GdeHGQc s)
(3ChdgG (B:s
(3CNHQfG GdTjN GHh eMeO GdMSf Hf Ydi Hf eMeO GdLhgQi bQCg Ydjg bGd gPG cJGH ENJjGQ aUjM GdcdGe eeG jLQi ai cdGe GdfGS hcJHge aefg eG ajg dZI hGMOg HGH aYdJ HaJM GdYjf s
(3BNQgG (B:s
(3hjbGd dg ef PhGJ GdMGaR GdQOL hjbGd dg ef PhGJ GdNa GdSNJ Je GdcJGH HMeO Gddg JYGdi hefg s
(3GdfSNI HgG MhGTs
(3Ydjg SeGYs
(3HBNQg bQGAIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs